The Concept of Islamic Civil Law in Indonesia: Definition, Scope of Discussion and Application - Dhini Permasari Johar, Rama; Sangeen, Qudratullah; Yulisa, Ike; Ichsan, Muhammad; Delia, Friska (Jurnal Elsyakhshi, 2025)
The concept of Islamic Civil Law in Indonesia is always interesting to discuss. This is because Islamic civil law as a positive law will continue to develop along with the development of society. This study aims to explain in more depth how the concept of Islamic civil law in Indonesia, starting from the definition of Islamic civil law in Indonesia, what is the scope of its discussion and how it is applied specifically in sharia economic disputes, especially in Religious Courts in West Sumatra. The type of research that the author conducted is qualitative research. The data analysis technique that the author used is thematic analysis. The data sources for this study are books or literature that are relevant to the discussion of the research and also data on sharia economic cases in Religious Courts throughout West Sumatra which the author took from the Case Tracking Information System on the website of each religious court, namely 18 religious courts in West Sumatra. The results of the study indicate that Islamic civil law in Indonesia is a set of positive legal rules that regulate individual interests that are specifically applied to Muslims in Indonesia. While the scope of the discussion is in marriage; inheritance; wills; grants; waqf; zakat; infaq; shadaqah; and sharia economics. In the first-level Religious Courts in regencies/cities throughout West Sumatra, 85 sharia economic cases have been handled in the period 2019-2024. The available data shows that the Talu Religious Court has the most cases, namely 18 cases.